MHR and NHR but not LHR were associated with coronary artery disease in patients with chest pain with controlled LDL-C. (October 2022) - Liu, Mengping; Liu, Xiaojun; Wei, Zhen; Hua, Rui; Huang, Yuzhi; Hao, Xiang; Yuan, Zuyi; Zhou, Juan
Several leukocyte to high-density lipoprotein cholesterol (HDL-C) ratios, including monocyte to HDL-C ratio (MHR), neutrophil to HDL-C ratio (NHR) and lymphocyte to HDL-C ratio (LHR), have been proposed as novel inflammatory indicators. We performed a cross-sectional study to investigate the relationships between these leukocyte to HDL-C ratios and coronary artery disease (CAD) in patients with chest pain with controlled low-density lipoprotein cholesterol (LDL-C). A total of 3482 patients with chest pain with LDL-C <1.8 mmol/L were enrolled. We evaluated the relationships between MHR, NHR, LHR and HDL-C and the occurrence of CAD as well as severe stenosis. We found that in patients with chest pain, higher MHR (adjusted OR=2.83, 95% CI 1.61 to 4.99, p<0.001) and NHR (adjusted OR=1.08, 95% CI 1.04 to 1.13, p<0.001), as well as lower HDL-C (adjusted OR=0.53, 95% CI 0.36 to 0.78, p=0.001), but not higher LHR (adjusted OR=1.06, 95% CI 0.94 to 1.20, p = 0.341), had a stronger association with the occurrence of CAD. Moreover, unlike LHR (adjusted OR=1.02, 95% CI 0.93 to 1.13, p=0.654), higher MHR (adjusted OR=2.10, 95% CI 1.43 to 3.07, p<0.001) and NHR (adjusted OR=1.06, 95% CI 1.04 to 1.09, p<0.001) and lower HDL-C (adjusted OR=0.38, 95% CI 0.26 to 0.56, p<0.001) were risk factors for severe stenosis. A receiver operating characteristic curve analysis exhibited comparable abilities between MHR and NHR in predicting the presence and severity of CAD. In conclusion, even though patients with chest pain have achieved LDL-C <1.8 mmol/L, the inflammatory indicators MHR and NHR maintained their predictive abilities and remained associated with the occurrence and severity of CAD.